DEMOCRACIES ON THE MOVE contributions to a social theory of democracy. - Millefiorini, Andrea (Routledge studies in political sociology., 2025)
This book enquires into the state of health of contemporary democracies, offering a sociological reading of democracy to identify the causes of the current transformation of democracy from a social and cultural perspective. With attention to the social dynamics present in modern Western societies, it analyses phenomena such as populism, new conspiracy theories and denialism, and processes including de-politicisation and de-democratisation. Identifying the centrality of questions concerning social identity and the political imaginary to our understanding of such phenomena, Democracies on the Move explores the mechanisms that link the transformations of today's societies to the current phase of crisis in Western democracies. It will therefore appeal to scholars of social and political theory and political sociology.